(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
BACKGROUND: Serum testing for IgG-mediated food intolerance is popular as an important component of clinical diagnosis and treatment in integrative medicine practice in Thailand. OBJECTIVES: To assess the prevalence of food-specific IgG antibodies and determine the most common type of food allergy among adult patients with chronic acne. METHOD: This was a cross-sectional study conducted at a dermatology clinic in Bangkok, Thailand between 2016 and 2020. SETTING: S-Mart Clinic (Anti-Aging and Wellness Center), Bangkok, Thailand (2016-2020). PATIENTS AND METHODS: This study included all patients who underwent serum testing for food-specific IgG antibodies between the years 2016 and 2020. MAIN OUTCOME MEASURE(S): Frequencies and median titers of each type of food-specific IgG antibody in all patients. RESULTS: A total of 299 patients were tested for food-specific IgG antibodies at the S-Mart Clinic between 2016 and 2020. The most common indications were chronic adult acne (103 patients, 34.4%) and chronic skin eruptions (105 patients, 35.1%). Among the patients, 237 (79.26%) were female, and 62 (20.74%) were male, with a mean age of 39.2 (+13.7) years. The most common types of food-specific IgG antibodies, with median titers above 23 U/ml, were cola nut (96.0% of patients, median titer = 53 U/ml), barley (92.3%, 49 U/ml), egg white (91.6%, 76 U/ml), Brewer’s yeast (85.6%, 49 U/ml), cow’s milk (85.3%, 82 U/ml), corn/maize (82.9%, 45 U/ml), pea (77.3%, 50 U/ml), pistachio (74.2%, 38 U/ml), wheat (73.9%, 33 U/ml), sheep’s milk (70.9%, 47 U/ml), casein, plum, and red kidney bean (69.9%, 64, 30, 33 U/ml), white haricot bean (65.9%, 34 U/ml), goat milk (60.2%, 36 U/ml), aloe vera (59.5%, 27 U/ml), cashew nut (55.6%, 26 U/ml), and almond (50.8%, 24 U/ml). The ranking of median titers for each type of food-specific IgG antibody correlated with their frequencies, except for cow’s milk (median titer = 82 U/ml), egg white (76 U/ml), and casein (64 U/ml), which had the highest median titers. The patterns of food types, frequencies, rankings, and median titers were consistent across all cases, the acne group, and the non-acne group. CONCLUSION: The most common indications for patients tested with food-specific IgG antibodies in this study were chronic adult acne and chronic skin eruptions. There were no statistically significant differences in the types of food, frequencies, rankings, and median titers among all cases, the acne group, and the non-acne group. LIMITATIONS: The data is limited to a single anti-aging clinic in Thailand and may not be representative of the entire practice in the country. Follow-up studies could not be conducted due to incomplete follow-up data, which prevented the assessment of the effects of eliminating these foods from the diet.